-4(x-3)=-4(3-x)

Simple and best practice solution for -4(x-3)=-4(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x-3)=-4(3-x) equation:


-4(x-3)=-4(3-x)

We simplify the equation to the form, which is simple to understand
-4(x-3)=-4(3-x)

Reorder the terms in parentheses
+(-4x+12)=-4*(3-x)

Remove unnecessary parentheses
-4x+12=-4+*(+3-x+)

Reorder the terms in parentheses
-4x+12=+(-12+4x)

Remove unnecessary parentheses
-4x+12=-12+4x

We move all terms containing x to the left and all other terms to the right.
-4x-4x=-12-12

We simplify left and right side of the equation.
-8x=-24

We divide both sides of the equation by -8 to get x.
x=3

See similar equations:

| 75+.10x=200+.05x | | 2/10×=20/1 | | 45-81/9 | | 3x-2=1/3 | | 3x-3=1/3 | | x(squared)-16= | | 3x+37=86 | | 5x-2y=13forx | | 6x+2y=47 | | (r^2)+4=-4r-19 | | 7x(3x/4) | | (4a-3)(2a+7)= | | 30w-(-w+6)+a(-5w+4)=-(5w+6)+(-8+3w) | | -6x+12+12-24=-36 | | 23x-14x+7=61 | | d=iqx | | y=3/2-1 | | 8x-3+6x=7x+5-9x | | .25x-35=50 | | 2x+2x+2=8x-14 | | 0=-2.5x+80 | | 21x+15-13x=-73 | | -n+8n=5n | | 9x+6x=195 | | 5(d+2)=3(d+-6) | | 2/5w | | 14+2x+6=24 | | 1.25x-6=x | | 9a-2=-3 | | 48n^3=147 | | 5x-4(4y-5x)+6y= | | 40=w^2+13w |

Equations solver categories